Thames tunnel to Channel Tunnel : 150 years of civil engineering : selected papers from the journal of the Institution of Civil Engineers published to celebrate its 150th anniversary - Howie, Will; Chrimes, Mike (Thomas Telford, 1987)
This volume provides 150 years of civil engineering as seen through a selection of some of the most influential papers published in the Proceedings of the Institution of Civil Engineers between two great engineering milestones.